PEMANFAATAN KELAS IBU HAMIL SEBAGAI MEDIA EDUKASI KESEHATAN IBU DAN ANAK - Susilawati Susilawati; Sriwidyastuti Sriwidyastuti; Sumarni Sumarni (Yayasan Nusantara Hasana Berdikari, 2026)
Efforts to reduce maternal and child mortality cannot be separated from the role of community empowerment, one of which is carried out through the implementation of Pregnant Women's Classes. The health of pregnant women is a major concern for the government. Pregnant women carry the future generation of the nation who will productively contribute greatly to the progress of the nation and state. Therefore, every pregnant woman requires care during her pregnancy. This community service activity was carried out at the Mattirowalie Village Health Post in Bone Regency, where the Pregnant Women's Class is one of the routine activities in the Maternal and Child Health Program. The purpose of this activity is an effective educational tool to increase knowledge about maternal and child health (MCH), nutrition, childbirth preparation, and newborn care. This education has been proven to improve mothers' abilities in early detection of pregnancy complications and optimizing the health of pregnant women. This program generally focuses on discussion and exchange of experiences. This community service was carried out on April 14, 2026, through group education. Consisting of 17 pregnant women, the material was delivered directly by the presenter. The result of this community service was an increase in knowledge about maternal health education through the mother's class.